1988
DOI: 10.1002/pssb.2221490253
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Expressions for the One‐Center Elements of Compton Profiles. Slater‐Type Orbitals

Abstract: Analytic Expressions for the One-Center Elements of Compton Profiles. Slater-Type 0 rbitals R. RAMfREZ2) and M. C. B O W BY The momentum distribution of electrons in atoms, molecules, and solids has been studied in the past years by inelastic Compton scattering with monochromatic X and r-ray radiation /1, 2/. Within the impulse approximation (IA) /3, 4/ the shape of the Compton line can be related to the directional Compton profile (DCP) . The IA is based on the following approximations: i) scattering of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Consequently several theoretical contributions to the study of atomic electron momentum distributions have been reported so far, including analytical expressions for electron momentum distributions of small atoms using Slater basis sets [13][14][15][16][17], as well as calculations of CP of elements at Hartree-Fock level (HF) using double-zeta and numerical wave functions [18,19]. Furthermore, total momentum expectation values and other p-space properties [20][21][22] have been computed, and more recently, Ozdogan and Eraslam have published analytical calculations of CP using Clementi Roothan-Hartree-Fock functions for atoms ranging from helium to neon [23].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently several theoretical contributions to the study of atomic electron momentum distributions have been reported so far, including analytical expressions for electron momentum distributions of small atoms using Slater basis sets [13][14][15][16][17], as well as calculations of CP of elements at Hartree-Fock level (HF) using double-zeta and numerical wave functions [18,19]. Furthermore, total momentum expectation values and other p-space properties [20][21][22] have been computed, and more recently, Ozdogan and Eraslam have published analytical calculations of CP using Clementi Roothan-Hartree-Fock functions for atoms ranging from helium to neon [23].…”
Section: Introductionmentioning
confidence: 99%